Cardiac and hepatic siderosis in myelodysplastic syndrome, thalassemia and diverse causes of transfusion-dependent anemia: the TIMES study. Issue 3 (June 2019) - Ho, P. Joy; Hiwase, Devendra; Ramakrishna, Raj; Viiala, Nicholas; Solterbeck, Ann; Traficante, Robert; Zor, Evren; Gervasio, Othon L.; High, Laura M.; Ross, David M.; Bowden, Donald K.
Abstract : Abstract: The significant morbidity and mortality associated with iron overload can be reduced by effective iron chelation. Magnetic resonance imaging (MRI) provides accurate and reproducible iron load assessment. The aim of this epidemiological study was to assess the prevalence and severity of cardiac and hepatic siderosis by MRI and to evaluate the impact of MRI on clinical management in patients with transfusion-dependent anemia and non-transfusion-dependent thalassemia (NTDT). We enrolled 243 patients with myelodysplastic syndromes (MDS), thalassemia major (TM), NTDT or other chronic anemia. Overall, 10% and 48% had cardiac and hepatic siderosis, respectively. Mean liver iron concentration (LIC) was above target range in all groups; mean myocardial T2 * was normal. Hepatic siderosis was more prevalent than myocardial siderosis in patients with MDS, occurring in 54.4% and 4.4% of patients, respectively. As also observed in patients with NTDT or other anemia, hepatic siderosis was present in a large proportion of MDS patients who were chelation naïve (57.7%), as well as in patients receiving iron chelation therapy (ICT) (52.4%), despite a lower transfusion load compared with TM. Correlation between LIC and serum ferritin was observed across diseases; however, not all patients requiring ICT could be identified with serum ferritin alone, as serum ferritin underestimated LIC in 4.4% and overestimated LIC in 7.5% of patients. Exploratory analyses showed serum ferritin thresholds for liver siderosis detected by MRI at approximately 300 ng/mL higher in MDS than in TM. Most patients reported low–medium adherence to ICT; MRI assessment led to change in ICT in 46% of evaluable patients, including 52% of MDS patients. Accurate organ iron monitoring by MRI facilitated appropriate initiation of chelation, dose optimization and clinical decision making. Trial registration: ClinicalTrials.gov: NCT01736540. Abstract : Supplemental Digital Content is available in the text